The Phenomenon of Graduonymy in Fels - Djumakuziyevna, Shermatova Gulnoza (European Journal of Life Safety and Stability (2660-9630), 2021)
Words in a graduonymic series can be ranked not only by some kind of sema, but also by several semas and stylistic paints, which are related to each other. On the graduonymic line there is a law of transition of quantitative changes to qualitative changes in the degree of increase and decrease of the sign by degrees.